2016
DOI: 10.3389/fpsyg.2016.02009
|View full text |Cite
|
Sign up to set email alerts
|

The Information and Communication Technology User Role: Implications for the Work Role and Inter-Role Spillover

Abstract: Management and organization research has traditionally focused on employees’ work role and the interface between their work and family roles. We suggest that persons assume a third role in modern society that is relevant to work and organizations, namely the Information and Communication Technology User (ICTU) role. Based on role theory and boundary theory, we develop propositions about the characteristics of this role, as well as how ICTU role characteristics are related to boundary spanning activity, inter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 153 publications
0
14
0
1
Order By: Relevance
“…In a different study, they investigated the altered susceptibility to placebo effects caused by Alzheimer’s disease by studying Alzheimer’s patients at the initial stage of the disease and 1 year later. They found that a smaller placebo response is predicted by reduced frontal connectivity 23 , 100 . Also, it is known that the experience of pain can be modulated by cognitive factors, such as beliefs and expectations, which is exactly evident in placebo analgesia 96 , 101 .…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, they investigated the altered susceptibility to placebo effects caused by Alzheimer’s disease by studying Alzheimer’s patients at the initial stage of the disease and 1 year later. They found that a smaller placebo response is predicted by reduced frontal connectivity 23 , 100 . Also, it is known that the experience of pain can be modulated by cognitive factors, such as beliefs and expectations, which is exactly evident in placebo analgesia 96 , 101 .…”
Section: Discussionmentioning
confidence: 99%
“…Work‐family conflict usually occurs when one's efforts to meet the demands of one's work role interfere with one's efforts to fulfil family demands, and vice versa. Recent research has suggested that work‐home conflict can be translated into other interrole conflicts, such as that between the ICT user role and the family role (Piszczek, Pichler, Turel, & Greenhaus, ). According to this view, stressors or strain generated in the ICT user role can spill over into the family role, affecting the latter role in an adverse way by diminishing role performance and increasing interpersonal conflict (Barber, Taylor, Burton, & Bailey, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, the constant rotation between what SHA users are preoccupied with in their ICT user role (ie, finding the right balance of accessibility in their SHA use) and what they have to take care of in their family role (eg, catering to family needs) may create interrole conflicts (Brevers et al, ; Piszczek et al, ). These conflicts may not only imply that users' time and attention are siphoned away from social behaviours at home that drive interpersonal satisfaction, such as fulfilling home responsibilities or spending time together.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…As mentioned before, studies have found that employees will adopt strategies to manage strain from competing work and family demands (Baltes, Zhdanova, & Clark, 2011; Clark et al., 2017). However, it is important to consider the workplace work–family climate because segmentation preferences may be associated with higher work‐to‐family conflict within particular contexts (Kossek et al., 2001; Piszczek, Pichler, Turel, & Greenhaus, 2016; Shockley et al., 2017), including a family sacrifice climate.…”
Section: Family Sacrifice Climatementioning
confidence: 99%